Evidence for the autophagy of microinjected proteins in HeLA cells (The Rockefeller University Press, 1977)
Rhodamine-conjugated proteins were microinjected into living HeLa cells. Fluorescence microscopy was then employed to study their segregation from the cytoplasm into lysosomes. Results obtained in this way were verified when the corresponding unconjugated proteins were localized by autoradiographic, histological, and antibody-staining methods after their microinjection. Most injected proteins were segregated into cytoplasmic granular structures during their removal from cells. As evidence that these were autophagic vacuoles, they were found to contain no detectable acid phosphatase activity upon formation, after which they moved to the juxtanuclear position of lysosomes and appeared to fuse with them. The segregation of microinjected proteins exhibited a high degree of selectivity. The half- times of placement of individual exogenous proteins into cytoplasmic granules varied from 3 h to nearly 3 days, and one protein, hemoglobin, was never observed to enter them. Furthermore, endogenous HeLa proteins in a size fraction near 200,000 daltons were segregated much more rapidly than those in a fraction near 40,000 daltons. In these studies, rapid protein segregation appeared to take place by a mechanism of exclusion of the injected protein from numerous cytoplasmic domains.